The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5435/jaaos-d-20-01268
|View full text |Cite
|
Sign up to set email alerts
|

LGBTQ+ in Orthopaedics: Creating an Open and Inclusive Environment

Abstract: Lesbian, gay, bisexual, transgender, and queer or questioning (LGBTQ1) individuals may encounter added challenges in the healthcare setting. Both providers and patients may face discrimination based on their sexual orientation or gender identity, which may lead to avoidance or delay in seeking care. LGBTQ1 physicians often choose not to disclose their sexual orientation because of concerns about harassment, isolation, and depression. Orthopaedic surgery remains the least diverse medical specialty and there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In the United States, LGBTQ+ individuals often encounter discrimination and stigmatization because of their sexual orientation and gender identity, impacting their workplace experiences and overall well-being [24,30,31,35]. Knowledge of LGBTQ+ practitioners' experiences in orthopaedics, particularly in terms of workplace openness about sexual and gender orientation and perceived experiences of bullying, discrimination, or differential treatment, remains limited despite acknowledged diversity gaps in our profession [6,15,20]. We aimed to gather demographic information and assess reported experiences of bullying, discrimination, and differential treatment toward LGBTQ+ individuals in orthopaedic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the United States, LGBTQ+ individuals often encounter discrimination and stigmatization because of their sexual orientation and gender identity, impacting their workplace experiences and overall well-being [24,30,31,35]. Knowledge of LGBTQ+ practitioners' experiences in orthopaedics, particularly in terms of workplace openness about sexual and gender orientation and perceived experiences of bullying, discrimination, or differential treatment, remains limited despite acknowledged diversity gaps in our profession [6,15,20]. We aimed to gather demographic information and assess reported experiences of bullying, discrimination, and differential treatment toward LGBTQ+ individuals in orthopaedic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a 2014 national climate survey of general surgery residents reported that 57% of LGBTQ+ residents concealed their sexual orientation from fellow residents and physicians because of fear of rejection or poor evaluations [25]. These findings show that LGBTQ+ physicians often choose not to disclose their sexual orientation because of concerns about harassment, isolation, and depression [6]. Chu et al's [6] review of evidence about LGBTQ+ experiences in orthopaedic healthcare revealed notable challenges that affected patients and providers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, I remain hopeful that as more transgender and gender-diverse athletes demonstrate the bravery required to risk everything for a life of authenticity, we as physicians will have the courage to support them. Through the recent formation of organizations such as Pride Ortho and research within orthopaedic surgery that focuses on the care of transgender and gender-diverse patients [3,4,7,10,16], our field demonstrates capacity and eagerness to provide exceptional care for all patients. It is not a risk to provide the highest level of care for patients subjected to disproportionate rates of discrimination within healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians should be attentive to the needs of sexual minority individuals, including members of the LGBTQIA+ community and men having sex with men (MSM) [90,91]. These populations have been disproportionately impacted and are still impacted by the HIV pandemic.…”
Section: Orthopedic Management Of Sexual Minority Individualsmentioning
confidence: 99%